Systematic Immunophenotyping Reveals Sex-Specific Responses After Painful Injury in Mice - Tawfik, Vivianne L.; Huck, Nolan A.; Baca, Quentin J.; Ganio, Edward A.; Haight, Elena S.; Culos, Anthony; Ghaemi, Sajjad; Phongpreecha, Thanaphong; Angst, Martin S.; Clark, J. David; Aghaeepour, Nima; Gaudilliere, Brice (Frontiers in Immunology, 2020)
Many diseases display unequal prevalence between sexes. The sex-specific immune response to both injury and persistent pain remains underexplored and would inform treatment paradigms. We utilized high-dimensional mass cytometry to perform a comprehensive analysis of phenotypic and functional immune system differences between male and female mice after orthopedic injury. Multivariate modeling of innate and adaptive immune cell responses after injury using an elastic net algorithm, a regularized regression method, revealed sex-specific divergence at 12 h and 7 days after injury with a stronger immune response to injury in females. At 12 h, females upregulated STAT3 signaling in neutrophils but downregulated STAT1 and STAT6 signals in T regulatory cells, suggesting a lack of engagement of immune suppression pathways by females. Furthermore, at 7 days females upregulated MAPK pathways (p38, ERK, NFkB) in CD4T memory cells, setting up a possible heightened immune memory of painful injury. Taken together, our findings provide the first comprehensive and functional analysis of sex-differences in the immune response to painful injury.